Phytoplankton species‐specific release of dissolved free amino acids and their selective consumption by bacteria. (13th May 2013) - Sarmento, Hugo; Romera-Castillo, Cristina; Lindh, Markus; Pinhassi, Jarone; Sala, M. Montserrat; Gasol, Josep M.; Marrase, Cèlia; Taylor, Gordon T.
Abstract : Despite representing only a small fraction of the ocean's dissolved organic matter pool, dissolved free amino acids (DFAA) have high turnover rates and are major nitrogen and carbon sources for bacterioplankton. Both phytoplankton and bacterioplankton assimilate and release DFAA, but their consumption and production are difficult to quantify in nature due to their short residence times (min) as dissolved monomers. We segregated DFAA production by phytoplankton and bacterial consumption by measuring individual DFAA concentrations in four axenic phytoplankton cultures during the exponential growth phase, and also after 4 d incubations in the presence of a natural bacterioplankton community. The amounts and composition of the DFAA pool varied widely among phytoplankton species. The proportion of dissolved organic carbon attributed to DFAA varied among cultures. The picoeukaryotic prasinophyte, Micromonas pusilla, released higher amounts of DFAA than the other species tested (diatoms and dinoflagellate), especially alanine, which has been reported as the dominant individual DFAA in some oligotrophic environments. Community structure of heterotrophic prokaryotes responded to differences in the quality of organic matter released among microalgal species, with Roseobacter ‐related bacteria responding strongly to exudate composition. Our results demonstrate the specificity of DFAA extracellular release among several algal species and their preferential uptake by members of bacterial communities.